Immature-to-total neutrophil ratio as an early diagnostic tool of bacterial neonatal sepsis - Darnifayanti Darnifayanti; Guslihan Dasa Tjipta; Rusdidjas Rusdidjas; Bugis Mardina Lubis (Paediatrica Indonesiana, 2015)
Background Bacterial sepsis is the main cause of morbidity and mortality in neonates. Early diagnosis and appropriate treatment for the condition can reduce mortality rates. Blood cultures are the gold standard to diagnose bacterial sepsis, but they require 3-5 days for results, whilst the disease may progress rapidly in neonates. Examination of immature-to-total neutrophil ratio (I/T ratio) in peripheral blood smears is a quicker and less expensive method to diagnose bacterial sepsis in neonates. Some studies found the sensitivity of I/T ratio to be 88%-90% in predicting bacterial spesis.Objective To assess the usefulness of the I/T ratio as an early diagnostic tool for neonatal bacterial sepsis.Methods This cross-sectional study was conducted from February to March 2011. Subjects were collected by consecutive sampling. Fifty-three neonates suspected to have bacterial sepsis in the Perinatology Unit at H. Adam Malik Hospital were included. Subjects underwent routine blood examinations, C-reactive protein level measurements, blood cultures, and peripheral blood smears. All statistical analyses were conducted with SPSS (version 16.0 for Windows).Results Of the 53 subjects, 26 had bacterial sepsis based on blood cultures. The I/T ratio had a sensitivity of 88.46%, specificity 81.84%, positive predictive value 82.14%, and negative predictive value 88%. The receiver operating characteristic curve showed a cut-off point of 83.3 (95%CI 71.3 to 95.3)%.Conclusion The I/T ratio may be a good alternative to blood cultures as an early indicator of bacterial neonatal sepsis, as it is faster, less expensive and has good sensitivity and specificity.